2015
DOI: 10.1088/1757-899x/89/1/012013
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation, strength and work hardening of age hardened aluminium alloys

Abstract: Abstract. The strength and work hardening of age hardened AA6063 and AA6082 alloys have been investigated in terms of a detailed characterization of precipitate and dislocation structures obtained by TEM and SEM. Tensile and compression tests were performed at as quenched, peak aged and severely aged conditions. A strong work hardening in the as quenched condition was found, similar to AlMg alloys with twice as much alloying elements in solid solution. It was found that the initial work hardening rate and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…Ryen et al . 16 showed that after large deformations, the needle-axis of β″ precipitates changed, indicating that they were uniformly sheared by dislocations. Furthermore, Poole et al .…”
Section: Introductionmentioning
confidence: 99%
“…Ryen et al . 16 showed that after large deformations, the needle-axis of β″ precipitates changed, indicating that they were uniformly sheared by dislocations. Furthermore, Poole et al .…”
Section: Introductionmentioning
confidence: 99%
“…The primary factors influencing the strengthening of the AA2519 alloy are grain size and the participation of the strengthening phase. The impact on the strengthening is greater in the case of the strengthened phase than in the case of the grain boundaries [ 11 ]. This may indicate that the evolution of the strengthening phase may result in a higher increase in the strengthening in rolling at room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…An important issue in the development of new, high-strength aluminum alloys is increasing the mechanical properties of precipitation-hardened alloys. In their basic condition, these alloys contain a strengthening phase in their structure, which is responsible for their high strength properties [ 10 , 11 , 12 ]. Excellent examples of these materials are AA2219-T87 (UTS = 470 MPa) and AA7075-T651 (UTS = 570 MPa) alloys, widely used in the aerospace and military industry [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…An example of research on the heat treatment of AlMgSi alloys is the article by Richert et al [22] concerning the new, multistage aging of the 6xxx series alloys. The studies of Ryen et al [23] showed the presence in alloys AA6063 and AA6068, after aging precipitations as B′, β″, U2, and U1, β′ and some unidentifiable crystal structures. Detailed studies of the precipitations in aluminum alloys are also presented in the work by Andersen et al [24].…”
Section: XXX Series Aluminum Alloys For Extrusion Of Shapesmentioning
confidence: 98%